Mushrooms as Potential Sources of Active Metabolites and Medicines - Bhambri, Anne; Srivastava, Malay; Mahale, Vivek G.; Mahale, Sushma; Karn, Santosh Kumar (Frontiers in Microbiology, 2022)
Background: Mushrooms exist as an integral and important component of the ecosystem and are very precious fungi. Mushroom has been traditionally used in herbal medicines from many centuries. There are various medicinal mushroom mentioned in the current work such as Trametes, Agaricus, Ganoderma, Hydnum, Coprinus, Morchella, Cantharellus, Amanita, Cortinarius, Tremella, Rigidoporus, Grifola, Lentinus, Pleurotus, Calocybe, Huitlacoche, Cordyceps etc which plays a vital role in various diseases and have several metabolite components and nutritional values. Therefore the finding, identification and metabolic characterization are important. Medicinal mushroom can be identified morphologically and can also be identified at molecularly by Internal Transcribed Spacer (ITS) regions gene sequencing. Recently are several other methods are included such as high pressure liquid chromatography, nuclear magnetic resonance spectroscopy, microscopy, thin-layer chromatography, DNA sequencing, gas chromatography-mass spectrometry, chemical finger printing, ultra-performance liquid chromatography, fourier transform infrared spectroscopy, liquid chromatography quadrupole time-of-flight mass spectrometry and high-performance thin-layer chromatography. Lately, matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) technique is also used for the identification of fungi. Mushrooms contain active metabolites such as for anti-oxidant, anti-cancer, anti-inflammatory, anti-aging, anti-tumor, anti-viral, anti-parasitic, anti-microbial, hepatoprotective, anti-HIV, anti-diabetic and many others mentioned in this review. This review will provide all the recent information of medicinal mushroom.